DIRECTIONS FOR DEVELOPING ENTREPRENEURIAL ACTIVITY IN AGRICULTURE (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article is based on the specific characteristics of agriculture and the role of entrepreneurship in it. It also studies and analyzes the opinions of scientists who have conducted scientific research in the field of agricultural entrepreneurship.